Stereoselective oxidative glycosylation of anomeric nucleophiles with alcohols and carboxylic acids - Tianyi Yang (Nature Portfolio, 2018)
Glycosylation of partially protected sugars is usually limited by suboptimal regio- and stereo-selectivities. Here, the authors show a general oxidative glycosylation between anomeric stannanes with a nonprotected hydroxyl group and oxygen nucleophiles, additionally providing mechanistic insights into the origin of selectivity.